Kompetensi Pendidik Dan Konvensionalisme Guru: Antara Inovasi Dan Tradisi - Natasya, Meila; Firdaus, Muhammad Imam; Khairani, Fatimah (EL-EMIR Institute, 2025)
In the era of 21st-century educational transformation, teachers are expected to be more than just transmitters of knowledge—they are required to act as agents of change capable of balancing pedagogical traditions with innovative teaching approaches. The urgency of this study lies in the need to understand how teacher competence influences the tendency to maintain conventional teaching methods, and how this affects the quality of learning. This research aims to examine the relationship between teacher competence and the persistence of conventionalism in teaching, while also identifying the potential integration of traditional values with innovative approaches. A qualitative research method was employed, utilizing classroom observations, in-depth interviews, and questionnaires distributed to 50 teachers from three different regions. The results reveal that most teachers still rely on traditional methods, but show openness to innovation when supported by training, facilities, and conducive policies. Tradition and innovation are proven to be synergized in contextual teaching practices.